Análise energética e econômica em uma agroindústria de laticínios - Lawder, José Henrique (2012)
This research constituted a case study related to an energy audit that was done in the Laticínios Guaíra Ltda company, a dairy producer industrial entity, located at Guaira city, western Paraná. Located in a region of high average temperatures in the summer season, the company needs to generate large-scale cold for dairy food production and preservation produced. This motivated us to do a close study about the transformation of energy within the company, plus a full diagnosis of end uses of the company such as driving force, cooling and lighting. The strategy of this work was to monitor the company's production process, indicating points of possible improvements in the work methodology of the unit. At the end of the study an analysis of technical and economic viability showed to the owners of the organization which actions could be able to take effect and the financial gain realized with these measures. The main results obtained with the recommendations of this audit were the reduction of 11.490,50 kWh per month in electricity consumption of the company, representing a monthly savings of R$ 2.191,35 in electricity bills. The conclusion of the study confirmed the economic viability of energy efficiency measures presented by replacing lamps and motors with more efficient ones. The discounted payback values of thirty months, the internal rate of return of 3.93% a month and cost-benefit ratio of 0.30 justify the economic feasibility of the proposed conservation measures.